Determinação de fósforo biodisponível em rações de peixes utilizando extração assistida por ultra-som e espectrofotometria no visível - Moraes, Paula M. De [UNESP]; Loureiro, Vanessa R. [UNESP]; Padilha, Pedro M. [UNESP]; Neves, Renato De Cássio F. [UNESP]; Saleh, Mayra A. D. [UNESP]; Santos, Felipe A. Dos [UNESP]; Silva, Fábio A. [UNESP] (Sociedade Brasileira de Química, 2009)
The aim of the present work was to develop and optimize a method for determination of bioavailable phosphorus in samples of feces and fish feed using ultrasound extraction and subsequent quantification by visible spectrophotometry. Using as extractor solution HNO3 0.50 mol L-1, the great conditions of extraction established were: sample mass - 100 mg, samples granulometry - < 60 µm, sonification time - five cycles of 40 s and ultrasound potency - 136 W. The proposed method was applied in studies of digestibility of this nutrient in different feeds used in diets of juvenile of Nile tilapia.
Determination of bioavailable phosphorus in fish feeds by ultrasound extraction and visible spectrophotometry
Keywords: ultrasound extraction; fish nutrition; phosphorus absorption